Pengaruh Self-Efficacy Enhancing Intervention Program (SEEIP) Secara Online Terhadap Self-Efficacy Dalam Manajemen Diri Penderita Diabetes Mellitus Tipe II Di Puskesmas Juli I - Siregar, Rinco; Gultom, Rumondang; Simamora, Marthalena; Pardede, Jek Amidos; Utari, Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The objectiveÂ of this study was to determine the effect of Self-Efficacy Enhancing Intervention Program (SEEIP) with online method on Self-Efficacy in Self-Management in Type 2 Diabetes Mellitus (T2DM) at Juli I Public Health CentreMethods: This study was a pre-experimental pre-test and post-test with only one group design. The population wasT2DM at Juli I Public Health Center in 2020. The sample size was 22 participants, selected by purposive sampling technique. Diabetes Management Self-Efficacy Scale (DMSES) was used to measure the Self-Efficacy in Self- Management of T2DM patients. Data were analyzed using paired t-testResults:Â The results of the study showed that the means score of Self- Management of T2DM before receiving SEEIP was 39,00 (SD: 15,455) and 90,23 (SD: 7,571)after receiving the SEEIP. Paired t-test showed that there was a significant difference on Self- Efficacy in Self-Management in T2DM at Juli I Public Health Centre in 2020Conclusion: Â SEEIP could improve self-efficacy in self-management for Type 2 diabetes mellitus at Juli I Public Health Centre.